A glutathione‐independent DJ‐1/PfpI domain‐containing tomato glyoxalaseIII2, SlGLYIII2, confers enhanced tolerance under salt and osmotic stresses. (26th November 2022) - Gambhir, Priya; Singh, Vijendra; Raghuvanshi, Utkarsh; Parida, Adwaita Prasad; Pareek, Amit; Roychowdhury, Abhishek; Sopory, Sudhir K.; Kumar, Rahul; Sharma, Arun Kumar
Abstract: In plants, glyoxalase enzymes are activated under stress conditions to mitigate the toxic effects of hyperaccumulated methylglyoxal (MG), a highly reactive carbonyl compound. Until recently, a glutathione‐dependent bi‐enzymatic pathway involving glyoxalase I (GLYI) and glyoxalase II (GLYII) was considered the primary MG‐detoxification system. Recently, a new glutathione‐independent glyoxalase III (GLYIII) mediated direct route was also reported in plants. However, the physiological significance of this new pathway remains to be elucidated across plant species. This study identified the full complement of 22 glyoxalases in tomato. Based on their strong induction under multiple abiotic stresses, SlGLYI4, SlGLYII2 and SlGLYIII2 were selected candidates for further functional characterisation. Stress‐inducible overexpression of both glutathione‐dependent ( SlGLYI4 + SlGLYII2 ) and independent ( SlGLYIII2 ) pathways led to enhanced tolerance in both sets of transgenic plants under abiotic stresses. However, SlGLYIII2 overexpression (OE) plants outperformed the SlGLYI4 + SlGLYII2 OE counterparts for their stress tolerance under abiotic stresses. Further, knockdown of SlGLYIII2 resulted in plants with exacerbated stress responses than those silenced for both SlGLYI4 and SlGLYII2 . The superior performance of SlGLYIII2 OE tomato plants for better growth and yield under salt and osmotic treatments could be attributed to better GSH/GSSG ratio, lower reactive oxygen species levels, and enhanced antioxidant potential, indicating a prominent role of GLYIII MG‐detoxification pathway in abiotic stress mitigation in this species. Summary statement: Stress inducible overexpression of glutathione‐independent SlGLYIII2 ‐mediated MG‐detoxification pathway outperforms glutathione‐dependent SlGLYI4‐SlGLYII2 overexpression mediated stress tolerance by maintaining a better GSH/GSSG ratio and lower ROS levels in tomato seedlings under abiotic stresses.